The Media Verification of Hoaxes about Human-Crocodile Conflicts - Herlina Agustin; Dadang Rahmat Hidayat; Dandi Supriadi; Rinda Aunillah (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2022)
The human-crocodile conflict frequently happens in Indonesia. Based on the data fromÂ http://www.crocodile-attack.info/, it is claimed that Indonesia is a country with the most cases of crocodile attacks. Mostly the attacks involved the saltwater crocodile (Crocodylus porosus). On the other hand, this conflict is worsened by the spread of inaccurate information among communities. From October 2019 to October 2021, there were 12 false stories about crocodile attacks. These hoaxes were distributed on social media, causing fear to those who consumed the information. It is crucial to be investigated, especially from the perspective of environmental journalism. This study describes how mainstream media outlets tried to clarify the hoaxes. The results show many materials contained by information disorder, which need to be clarified by the media to ensure clarity and truth for the public. This study finds that most mainstream media still have their conscience to protect the public from false information. It was done by practicing curation journalism that includes the discipline of verification. In conclusion, the media and information sources need to have a good comprehension of crocodile behavior. The research also catches the need for environmental journalism training for media practitioners in Indonesia. Thus, the media will be able to offer the best solution for reducing the attack while at the same time giving adequate education for the public to live in harmony with Indonesian flora and fauna.